Preoperative systemic immune-inflammation index may predict prolonged mechanical ventilation in patients with spontaneous basal ganglia intracerebral hemorrhage undergoing surgical operation - Xiao, Huaming; Li, Lei; Zhang, Feng; Cheng, Lei; Li, Yang; Han, Wenlan; Li, Huanting; Fan, Mingchao (Frontiers in Neurology, 2023)
Background Prolonged mechanical ventilation (PMV) has been proven as a risk factor for poor prognosis in patients with neurocritical illness. Spontaneous basal ganglia intracerebral hemorrhage (ICH) is one common subtype of hemorrhagic stroke and is associated with high morbidity and mortality. The systemic immune-inflammation index (SII) is used as a novel and valuable prognostic marker for various neoplastic diseases and other critical illnesses. Objective This study aimed to analyze the predictive value of preoperative SII for PMV in patients with spontaneous basal ganglia ICH who underwent surgical operations. Methods This retrospective study was conducted in patients with spontaneous basal ganglia ICH who underwent surgical operations between October 2014 and June 2021. SII was calculated using the following formula: SII = platelet count × neutrophil count/lymphocyte count. Multivariate logistic regression analysis and receiver operating characteristics curve (ROC) were used to evaluate the potential risk factors of PMV after spontaneous basal ganglia ICH. Results A total of 271 patients were enrolled. Of these, 112 patients (47.6%) presented with PMV. Multivariate logistic regression analysis showed that preoperative GCS (OR, 0.780; 95% CI, 0.688–0.883; P < 0.001), hematoma size (OR, 1.031; 95% CI, 1.016–1.047; P < 0.001), lactic acid (OR, 1.431; 95% CI, 1.015–2.017; P = 0.041) and SII (OR, 1.283; 95% CI, 1.049–1.568; P = 0.015) were significant risk factors for PMV. The area under the ROC curve (AUC) of SII was 0.662 (95% CI, 0.595–0.729, P < 0.001), with a cutoff value was 2,454.51. Conclusion Preoperative SII may predict PMV in patients with spontaneous basal ganglia ICH undergoing a surgical operation.